Manajemen Sumber Daya Manusia dalam Peningkatan Mutu Pendidikan di Perguruan Tinggi - Kadek Hengki Primayana (UHN IGB Sugriwa Denpasar, 2015)
Human resources management is very important in improving the quality of education. With the support of qualified resources, the university can go forward and develop. Improving the quality of education is determined by the leadership of educational institutions in managing their human resources. In the management of human resources, university leaders be key in improving the quality of education. University leaders are required to always develop human resources to create quality education.